Performance of palm oil clinker lightweight aggregate concrete comprising spent garnet as fine aggregate replacement - Nur Farah Aziera, Jamaludin; Khairunisa, Muthusamy; Mohd Faizal, Md Jaafar; Putra Jaya, Ramadhansyah; Mohamed A., Ismail (Hindawi, 2022)
The increase in building activity as a result of population expansion has resulted in an overexploitation of aggregate, with disastrous environmental consequences. Simultaneously, the disposal of spent garnet by the shipbuilding industry and palm oil clinker by palm oil mills harms the environment and needs a greater amount of landfill space. Therefore, the purpose of this study was to determine the influence of spent garnet as a fine aggregate substitute on the fresh, mechanical, and durability properties of palm oil clinker concrete. Concrete mixes were created using various percentages of spent garnet as a fine aggregate substitute, including 0%, 10%, 20%, 30%, and 40%. )e workability, compressive strength, flexural strength, splitting tensile strength, modulus of elasticity, water absorption, and acid resistance of the water cured concrete were all determined. It was determined that using 20% spent garnet increased the compressive strength of lightweight concrete. )e positive filler effect of spent garnet resulted in a densely packed internal structure of concrete, allowing it to have the lowest percentage of water absorption. )e same mixtures exhibited the least mass change and strength reduction when exposed to acid solution. )e results established that ecologically friendly concrete may be manufactured by including considerable volumes of waste from the shipbuilding and palm oil sectors